Effects of Selected Antioxidants on Electroretinography in Rodent Diabetic Retinopathy - Radosław Dutczak; Marita Pietrucha-Dutczak (Antioxidants)
Electroretinography (ERG) is a non-invasive technique for evaluating the retinal function in various ocular diseases. Its results are useful for diagnosing ocular disorders and assessing disease progression or treatment effectiveness. Since numerous studies are based on animal models, validating the ERG results from animals is pivotal. The first part of this paper presents basic information on the types of ERG tests used on rodents, and the second part describes the recorded functional changes in rodents’ retinas when various antioxidant treatments for diabetic retinopathy were used. Our study showed that among the tests for diabetic retinopathy diagnosis in rodents, full-field ERG is accurate and the most commonly used, and pattern ERG and the photopic negative response of the flash ERG tests are rarely chosen. Furthermore, antioxidants generally protect retinas from functional losses. Their beneficial influence is expressed in the preserved amplitudes of the a- and b-waves and the oscillatory potentials. However, prolonging the drug exposure showed that the antioxidants could delay the onset of adverse changes but did not stop them. Future studies should concentrate on how long-term antioxidant supplementation affects the retinal function.